URGENSI PENDIDIKAN KARAKTER DALAM DONGENG (Studi Kasus Buku Dongeng Komisi Pemberatasan Korupsi Seri Peternakan Kakek Tulus) - Fitri S. Isbandi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2017)
Storytelling is the oldest art’s heritage that is now to be forgotten by a half of people. Though, storytelling need to be preserved and developed as one of good activity that can support social interests extensively. Storytelling is fun activity but people rarely do it. Society development and social changes seems effect on decreasing of storytelling activities, not only at home, schools, worship place, playground but also library.